2019
DOI: 10.1590/s0004-2803.201900000-74
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Indicators of Malnutrition in Hospitalized Patients

Abstract: BACKGROUND: Malnutrition is associated with clinical factors, including longer hospital stay, increased morbidity and mortality and hospital costs. OBJECTIVE: To investigate the prevalence of malnutrition using different nutritional indicators and to identify factors that contribute to malnutrition in hospitalized patients. METHODS: We investigated anthropometric, laboratory standards, nutritional risk screening (NRS), subjective global assessment (SGA), mini nutritional assessment and habitual energy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
2
6
0
7
Order By: Relevance
“…Although there are limits to the use of BMI as an indicator of malnutrition, 27 BMI may be an effective indicator of nutrition status in patients with SRM, given the high prevalence of BMI‐defined underweight in our study. This finding is consistent with a 2019 study in elderly inpatients that reported an association between low weight by BMI and nutrition risk by the Nutrition Risk Screening 2002 tool 28 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although there are limits to the use of BMI as an indicator of malnutrition, 27 BMI may be an effective indicator of nutrition status in patients with SRM, given the high prevalence of BMI‐defined underweight in our study. This finding is consistent with a 2019 study in elderly inpatients that reported an association between low weight by BMI and nutrition risk by the Nutrition Risk Screening 2002 tool 28 …”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a 2019 study in elderly inpatients that reported an association between low weight by BMI and nutrition risk by the Nutrition Risk Screening 2002 tool. 28 More than half of the patients with SRM had a history of substance abuse. Prevalence of substance abuse was 57.1% in the patients with SRM that were not readmitted and 87.5% in those who were readmitted, whereas the 2018 US adult population estimate for illicit drug abuse was only 3%.…”
Section: Discussionmentioning
confidence: 99%
“…1 Besides, malnutrition could also be responsible. Low lymphocyte counts qualify as a factor associated with nutritional risk 21 whilst COPD severity is positively correlated with malnutrition. 22 A vicious circle produced by neurohumoral activation and the immune…”
Section: Discussionmentioning
confidence: 99%
“…14,19,20 The result of our study could be explained by the higher prevalence of malignancies among men and greater weight loss in men than in women during hospitalization. Although malnutrition often accompanies older age, and older patients are at increased risk for malnutrition at both, admission and discharge, 8,[21][22][23] in our patients average age was similar for malnourished and non-malnourished patients at discharge. In the study of Kang, malnutrition was higher in the patients over 70 years, while Zhu showed that malnutrition at discharge was significantly higher at age 65 and older.…”
Section: Risk Factors For Malnutritionon During Hospitalizationmentioning
confidence: 45%